Mathematical modeling of tomographic scanning of cylindrically shaped test objects; IOP Conference Series: Materials Science and Engineering; Vol. 363 : Cognitive Robotics - Kapranov B. I. Boris Ivanovich; Vavilova G. V. Galina Vasilievna; Volchkova A. V. Anastasia Valentinovna; Kuznetsova I. S. Irina Sergeevna (2018, 2018)
Title screen